The Quest for Teachers’ perception and Implementation of Discovery Learning in Indonesian Senior High Schools - Iskandar; Andi Anto , Patak (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2021)
Central to the implementation of educational change are the teachers, regardless of their position in the implementation policy, either as policymakers or as implementers. They may choose to implement or not to implement the policy in their classrooms since they do this behind closed doors. Their perceptions on the innovation are vital, and ultimately affect the successor the failure of the innovation. This study aimed at investigating Senior High School English teachers’ perceptions on the Discovery Learning (DL) as a recommended teaching model of English in Indonesian 2013 curriculum, and to what extent they implemented this model in their classrooms. Adopting qualitative inquiry, this study employed an ethnographic interview. It was evident that teachers perceived the DL model as an innovative model and in line with student-centered paradigm currently adopted in the 2013 curriculum. However, most teachers admitted they only occasionally used this model since it requires students to possess a number of cognitive skills and be intrinsically motivated to learn. Besides, this model requires high technology in which their schools still got difficulties providing technology-based tools to facilitate students’ learning